Evaluating a nursing communication skills training course: The relationships between self-rated ability, satisfaction, and actual performance - Mullan, Barbara; Kothe, E. (Churchill Livingstone, 2010)
Effective communication is a vital component of nursing care, however, nurses often lack the skills to communicate with patients, carers and other health care professionals. Communication skills training programs are frequently used to develop these skills. However, there is a paucity of data on how best to evaluate such courses. The aim of the current study was to evaluate the relationship between student self rating of their own ability and their satisfaction with a nurse training course as compared with an objective measure of communication skills. 209 first year nursing students completed a communication skills program. Both qualitative and quantitative data were collected and associations between measures were investigated. Paired samples t-tests showed significant improvement in self-rated ability over the course of the program. Students generally were very satisfied with the course which was reflected in both qualitative and quantitative measures. However, neither self-rated ability nor satisfaction was significantly correlated with the objective measure of performance, but self-rated ability and satisfaction were highly correlated with one another. The importance of these findings is discussed and implications for nurse education are proposed.